Pengembangan E-Modul Interaktif Fisika Berbasis Heyzine Flipbook untuk Meningkatkan Keterampilan Proses Sains Peserta Didik SMA - Hasan, Yulia; Susilawati; Yayuk Andayani (Lembaga Einstein College (LEC), 2025)
This study aims to develop an interactive physics e-module based on Heyzine Flipbook to strengthen the science process skills of high school students. The method used is research and development (R&D) with the 4D model (Define, Design, Develop, and Disseminate). The define stage is carried out by analyzing the needs and characteristics of students, while the design stage includes designing interactive displays and content based on videos, simulations, and digital quizzes. The develop stage involves expert validation and field trials, while the disseminate stage is carried out through teacher training and product distribution to partner schools. The results indicated that the developed interactive e-module was considered very valid with an average score of 3.82, very practical with a percentage of 91.60%, and effective in improving science process skills with an N-gain value of 0.67 in the medium category. This e-module also received positive responses from teachers and students because its display is attractive, simple to access, and helps understand abstract physics concepts. Thus, the interactive e-module based on Heyzine Flipbook is suitable for use as an innovative learning medium that can support the development of science process skills and improve the quality of physics learning in schools.